2018
DOI: 10.1016/j.abrep.2018.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Vaping associated with healthy food words: A content analysis of Twitter

Abstract: E-cigarettes were initially introduced as a less harmful alternative to combustible cigarettes, but marketing efforts may now be exceeding these claims by associating e-cigarettes with words related to healthy foods. These associations could mislead people to assume vaping is a healthy practice. Tweets from January to March 2017 were obtained from the Twitter Streaming Application Programming Interface (API) to assess content about vaping linked to healthy food words. Tweets were classified into one of nine ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The paper makes a contribution to psycholinguistics, while the findings might be also used in marketing. The content analysis of Twitter, done by T. Basáñez et al (2018), was aimed at examining tweets about e-cigarettes and vaping. The scholars used a pattern of analysis similar to the one employed in the current research.…”
Section: Introductionmentioning
confidence: 99%
“…The paper makes a contribution to psycholinguistics, while the findings might be also used in marketing. The content analysis of Twitter, done by T. Basáñez et al (2018), was aimed at examining tweets about e-cigarettes and vaping. The scholars used a pattern of analysis similar to the one employed in the current research.…”
Section: Introductionmentioning
confidence: 99%
“…Kong et al (2015) concluded about half of the vape trick videos on YouTube were industry-sponsored and all were youth-accessible. Basáñez et al (2018) categorized and compared 1,205 vaping tweets. They found vaping-promoting themed tweets ("health-enhancing," "youth-resonant," "sensations," or "harmless") were statistically more likely to originate from a marketing source than smoking prevention tweets (cessation use or anti-vaping).…”
mentioning
confidence: 99%
“…For older adults exposed to cigarette smoke, all these intakes of antioxidant micronutrients could be associated with the modulation of lung function decline. A lot of marketing efforts from tobacco industry are directed towards associating e-cigarettes with words related to healthy foods that are enhancing previous messages and promoting e-cigarettes as less harmful option versus traditional cigarettes as well as misleading people (11). In addition, a strange message that e-cigarettes deliver vitamins has been circulating (12) and social media is full of messages associating vaping with healthy eating habits such as salads (13).…”
mentioning
confidence: 99%